Investigating the Correlation Between Influencing Factors Affecting Students’ Interest in Learning and Academic Performance in Mathematics - Marbella, Mary Bernadine; Cruz, Yvonne (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to determine the factors influencing pupils’ interest in learning Mathematics and differences in pupils’ mathematics performance when grouped according to their subject of interest and subject with difficulty. The respondents of the study were the 183 randomly selected Grade VI pupils of the 10 Elementary Schools in Cluster 9 of the Division of Guihulngan City for the school year 2023-2024. The researcher utilized the descriptive correlational survey method and a validated researcher-made questionnaire. The instrument underwent reliability testing using the test-retest method with a gap of two weeks from its initial administration. Results of the test revealed coefficient stability of 0.95 (teaching pedagogy), 0.93 (utilization of learning resources), 0.91 (assessment strategies), and 0.92 (performance task). The researcher adhered to and observed the ethical guidelines outlined by Foundation University’s Ethics Committee. Consultation was pursued to ensure the research issue becomes clearly sound, significant, and ethically proper. The following statistical tools were used: percentage and frequency, weighted mean, mean, Kruskall-Wallis H-test, and t-test. The study then revealed that the following factors have a very high influence on pupils’ interest in learning Mathematics: (a) Teaching Pedagogy, (b) Utilization of Learning Resources, (c) Assessment Strategies, and (d) Performance Task. Data revealed that pupils’ performance in Mathematics based on grades is within the very satisfactory level. Moreover, a significant relationship exists between the earlier factors that influenced pupils’ interest in learning Mathematics and their Mathematics performance. Results further showed substantial differences in pupils’ Mathematics performance when grouped according to their subject of interest and subject with difficulty. At the same time, pupils’ demographic profiles cannot account for the differences in pupils’ Mathematics performance.